2015
DOI: 10.3892/ol.2015.3106
|View full text |Cite
|
Sign up to set email alerts
|

Brain perfusion and permeability in patients with advanced, refractory glioblastoma treated with lomustine and the transforming growth factor-β receptor I kinase inhibitor LY2157299 monohydrate

Abstract: Abstract. Transforming growth factor-β (TGF-β) signaling is associated with tumor progression and vascularization in malignant glioma. In the present study, magnetic resonance imaging was used to evaluate changes in the size and vascularity of glioblastomas in 12 patients who were treated with lomustine and the novel inhibitor of TGF-β signaling, LY2157299 monohydrate. A response in tumor size was observed in 2 of the 12 patients; in 1 of these 2 patients, a reduction in vascular permeability and perfusion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Traditionally, TGF-β 2 has been the preferred isoform for its role in glioma genesis and clinical trials specifically targeting this isoform have been carried out [ 25 ]. However, this treatment strategy seems to have lost the interest of researchers to the benefit of LY2157299, a TGF-β receptor 1 kinase inhibitor, which has yet to prove its efficiency ( identifier NCT01220271) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, TGF-β 2 has been the preferred isoform for its role in glioma genesis and clinical trials specifically targeting this isoform have been carried out [ 25 ]. However, this treatment strategy seems to have lost the interest of researchers to the benefit of LY2157299, a TGF-β receptor 1 kinase inhibitor, which has yet to prove its efficiency ( identifier NCT01220271) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in two patients with radiographic responses, a site-specific imaging study found that tumor blood flow was changed, similar to that seen with antiangiogenic agents. 104 However, compared with other antiangiogenic drugs, the blood flow changes occurred at a later time.…”
Section: Fhd Study and Early Clinical Development Of Galunisertib In mentioning
confidence: 99%
“…The small molecule inhibitor (SMI) galunisertib (LY2157299 monohydrate) showed anti-tumor effects in glioblastoma animal models and also in patients [ 10 , 11 , 12 , 13 , 14 , 15 ]. Galunisertib targets the serine-threonine kinase of the TGF-βRI and abrogates the phosphorylation of SMAD2, the initial intracellular protein of the TGF-β signaling pathway [ 12 ].…”
Section: Introductionmentioning
confidence: 99%